Initial oxidation of Ni-based superalloy and its dynamic microscopic mechanisms: The interface junction initiated outwards oxidation. (15th August 2021) - Zhai, Yadi; Chen, Yanhui; Zhao, Yunsong; Long, Haibo; Li, Xueqiao; Deng, Qingsong; Lu, Hui; Yang, Xiaomeng; Yang, Guo; Li, Wei; Yang, Luyan; Mao, Shengcheng; et al.
Abstract: Understanding the high-temperature initial oxidation mechanism and its dynamic processes is generally important because a small amount of initial oxidation can induce rapid corrosion and cause catastrophic failure. We reveal the mechanism of initial oxidation in a third-generation Ni-based superalloy by in situ visualizations and investigations of the nano- and atomic-scale dynamic processes from room temperature to 900 °C with a Cs-corrected environmental transmission electron microscope. The initial oxidation starts from the γ/γ′ interface at low temperatures. The high-temperature oxidation process with deficient oxygen prefers oxidation sites at the cross-junctions of the γ/γ′ interfaces. The growth rate of the oxide nanoparticles depends on the oxidation temperatures, with a low rate below 600 °C and a rapid-growth speed at temperatures higher than 700 °C. Mass transfer from the γ′ and γ phases to the γ/γ′ interface, particularly at the cross-junctions of these interfaces, is observed to cause oxide accumulation. This study provides a direct observation of the interphase, interface-junction-initiated outward oxidization including Al and Cr elements. These results shed light on the initial oxidation mechanisms of materials containing a second phase with interphase interfaces and the materials at deficient oxygen conditions as well as those with protection coating layers. Graphical abstract: Image, graphical abstract